Letter to Jane Tolmach from Joseph R. Cerrell - Joseph R. Cerrell:::::: (1961)
A letter to Jane Tolmach from Joseph R. Cerrell. The letter informs Jane that her request meet Senator H.M. Jackson for dinner.